Propagation of Love Waves in a medium containing a heterogeneous layer (MAUSAM, 1969)
Love wave propagation in a medium consisting of a heterogeneous layer of a finite depth embedded between a homogeneous layer and a half space has been studied. SH-displacement due to an infinite line source on the free surface has also been investigated.